A survey of awareness and adoption of artificial intelligence journalism among Lagos and Kwara States journalists - Bello, PhD, Semiu; Salaudeen, Abdullah; Umeaku, Perpetua Chinonye (The Indonesian Journal of Communication Studies, 2023)
Artificial Intelligence (AI) has become a transformative force in various industries worldwide, and journalism is no exception. This technological advancement has the potential to revolutionize the field of journalism by enhancing efficiency and accuracy in news reporting. In this study, the researchers leveraged the strength of the diffusion of innovation theory. The survey method was adopted to examine journalists' level of awareness and adoption of AI in their journalistic engagements and their perception of the likely impacts of AI on conventional journalism practice. With a survey of 376 journalists in Lagos and Kwara States, Nigeria, the study found a high awareness of artificial intelligence journalism among Lagos and Kwara States journalists in Nigeria. However, only a few have adopted the innovation in their day-to-day practice. This is because of the perceived professional and ethical challenges that undermine journalists' ingenuity, creativity, and skillfulness. Therefore, the study recommended that journalists and media stakeholders embrace artificial intelligence in journalism practice for effective and efficient outcomes.